Mechanical and Morphological Analysis of 3D-Printed Polylactic Acid-Polybutylene Adipate Terephthalate Composite - Raju, Suchetha N.; Devi, S.H. Kameshwari; Ajeya, K.P.; Prashantha, K. (Journal of Research Updates in Polymer Science, 2026)
In this research paper, a detailed examination of the mechanical properties and morphologies of PLA and PBAT polymer blend materials which were produced through 3D printing techniques was conducted. The examination was completed using a PLA/PBAT/Joncryl blended material with a composition ratio of 77/20/3 wt% and manufactured through FDM techniques and an experimental design technique known as the Taguchi method to evaluate the effects of various manufacturing parameters on the mechanical characteristics of the material. This study investigates the mechanical and morphological performance of FDM-printed PLA/PBAT/Joncryl blend specimens using a Taguchi L9 design. A PLA/PBAT/Joncryl blend (77/20/3 wt%) was fabricated and printed by varying layer height (0.16–0.24 mm), printing temperature (190–210 °C), and infill density (50–100%). The optimal condition (0.16 mm, 210 °C, 100% infill) produced a maximum tensile strength of 41.20 N/mm² and elongation of 12.42%. ANOVA results confirmed infill density as the most significant parameter contributing 81.35% of the variance (P = 0.009). SEM revealed reduced voids and improved interlayer fusion at higher infill levels, while DMA showed higher storage modulus ( 2200 MPa) for 100% infill specimens. The findings provide a process–structure–property relationship for optimizing biodegradable PLA/PBAT components for high-strength applications. This study illustrates that the infill % is the primary parameter that should be adjusted, while the layer height and printing temperature contribute but to a lesser extent to the improved performance of biodegradable PLA/PBAT/Joncryl blends.